Effect of DNA bending on transcriptional interference in the systems of closely spaced convergent promoters - Koroleva, Olga N.; Dubrovin, Evgeniy V.; Yaminsky, Igor V.; Drutsa, Valeriy L. (Biochimica et biophysica acta, 2016)
Over the past years there are increasing evidences that the interplay between two molecules of RNA polymerases, initiating transcription from promoters, oriented in opposite (convergent) directions, can serve as a regulatory factor of gene expression. The data concerning the molecular mechanisms of this so-called transcriptional interference (TI) are not well understood. The interaction of RNA polymerase with circular DNA templates, containing the convergent promoters, was investigated in a series of in vitro transcription assays and atomic force microscopy (AFM). In this work, to study the mechanisms of transcription interference a series of plasmids with oppositely oriented closely spaced artificial promoters, recognized by Escherichia coli RNA polymerase, was constructed. The constructs differ in promoter structure and distance between the transcription start sites. We have demonstrated that the transcripts ratio (RNA-R/RNA-L) and morphology of convergent open promoter complexes (OPC) are highly dependent on the interpromoter distance. The obtained results allowed us to suggest the novel model of TI, which assumes the DNA bending upon binding of RNA polymerase with promoters and explains the phenomenon of complete inactivation of weaker promoter by the stronger one. The results show that the conformational transitions in DNA helix, associated with DNA bending upon binding of RNA polymerase with promoters, play crucial role in OPC formation in the systems with convergent promoters. [Display omitted] •A series of plasmids with closely spaced convergent promoters is constructed.•Transcripts ratio (RNA-R/RNA-L) is highly dependent on interpromoter distance.•AFM morphology of two close open promoter complexes depends on interpromoter distance.•The new model of transcriptional interference was proposed.•This model assumes DNA bending upon binding of RNA polymerase with promoters.